Synthesis and Assessment of CO‐Release Capacity of Manganese Carbonyl Complexes Derived from Rigid α‐Diimine Ligands of Varied Complexity. Issue 30 (30th September 2015) - Jimenez, Jorge; Chakraborty, Indranil; Mascharak, Pradip K.
Abstract: Four manganese carbonyl complexes of the type [MnBr(CO)3 (NN)] (NN = α‐diimine ligands): namely [MnBr(CO)3 (bpy)] (1 ), [MnBr(CO)3 (phen)] (2 ), [MnBr(CO)3 (dafo)] (3 ), and [MnBr(CO)3 (pyzphen)] (4 ) (where bpy = bipyridine, phen = 1, 10‐phenanthroline, dafo = 4, 5‐diazafluoren‐9‐one, and pyzphen = pyrazino[2, 3‐ f ][1, 10]‐phenanthroline) have been synthesized and structurally characterized. These four complexes, each containing the fac ‐[Mn(CO)3 ] motif, release CO upon illumination with low‐power visible and UV light. The CO release rates and the absorption maxima of the complexes are, however, very similar, despite the systematic increase in structural complexity in the rigid α‐diimine ligand frameworks. This contrasts strongly with manganese carbonyl complexes derived from α‐diimine ligands in which at least one of the imine functions is not part of a rigid ring system. The results of this study should provide help in the future design of ligand frameworks suitable for the syntheses of photoCORMs to deliver CO to biological targets under the control of light. Abstract : The rates of CO photorelease from Mn I carbonyl complexes based on rigid α‐diimine ligands are quite similar to one another despite significant variations in the ligand frameworks.